Chronic exercise remodels the lysine acetylome in the mouse hippocampus - Qian, Ping; Ma, Feifei; Zhang, Wanyu; Cao, Dingding; Li, Luya; Liu, Zhuo; Pei, Pei; Zhang, Ting; Wang, Shan; Wu, Jianxin (Frontiers in Molecular Neuroscience, 2022)
Physical exercise benefits hippocampal function through various molecular mechanisms. Protein acetylation, a conserved and widespread post-translational modification, is involved in the synaptic plasticity and memory. However, whether exercise can change global acetylation and the role of acetylated proteins in the hippocampus have remained largely unknown. Herein, using healthy adult mice running for 6 weeks as exercise model and sedentary mice as control, we analyzed the hippocampal lysine acetylome and proteome by Liquid chromatography-tandem mass spectrometry. As a result, we profiled the lysine acetylation landscape for the hippocampus and identified 3,876 acetyl sites and 1,764 acetylated proteins. A total of 272 acetyl sites on 252 proteins were differentially regulated by chronic exercise, among which 18.58% acetylated proteins were annotated in mitochondria. These proteins were dominantly deacetylated and mainly associated with carbon-related metabolism, the Hippo signaling pathway, ribosomes, and protein processing. Meanwhile, 21 proteins were significantly expressed and enriched in the pathway of complement and coagulation cascades. Our findings provide a new avenue for understanding the molecular mechanisms underlying the benefits of exercise for hippocampal function and can contribute to the promotion of public health.